Auditoría de Gestión al Departamento de Talento Humano del Gobierno Autónomo Descentralizado del Cantón Nangaritza, de la Provincia de Zamora Chinchipe, Periodo 2021 - Jiménez Abad, Dennise Malena (2023)
The present work of Curricular Integration, called "MANAGEMENT AUDIT TO THE DEPARTMENT OF HUMAN TALENT OF THE AUTONOMOUS DECENTRALIZED GOVERNMENT OF THE NANGARITZA CANTON, OF ZAMORA CHINCHIPE PROVINCE, PERIOD 2021", was developed to fulfill the objectives; therefore, a diagnosis was applied to the Human Resources Department to know and analyze if the department applies management indicators, which will help determine the efficiency and effectiveness of its functions. Subsequently, the phases of the Performance Audit were developed: Preliminary Planning, Specific Planning, Execution, Communication of Results and Follow-up. Finally, a performance audit report was prepared containing the conclusions and recommendations that will serve as a reference to improve the recruitment, selection and hiring process and to issue a report so that the institution's highest authority can optimize institutional management. The Management Audit of the Human Resources Department was aimed at fulfilling the proposed objectives, which were fully met, starting with the Preliminary Knowledge phase, which allowed to know the entity directly, since the interview technique was applied to the Mayor and the highest authority of the department and personnel of this area, which allowed to collect relevant information, followed by the Planning phase, where the internal control was evaluated and programs were developed. In the Execution phase, the procedures established in the audit programs were applied, the findings that served as evidence to support the conclusions were determined. Then, in the Communication of Results the report was prepared with the respective Conclusions and Recommendations. Finally, in the follow-up phase a Schedule of Compliance and Application of Recommendations was prepared, which will serve to strengthen the Internal Control system of this institution. From the results obtained based on the Curricular Integration Work, it is concluded that in the entity under study, part of the staff of the Municipal Government does not perform functions that are under their professional profile, since they started working in the entity they are working in the same jobs. Therefore, there is no rotation of functions, they do not receive adequate training because they do not have a training schedule; during the period under analysis, no management indicators have been applied to determine the degree of compliance of specific activities in acceptable terms of efficiency and effectiveness; because of these new developments, it is recommended that the Decentralized Autonomous Government of Nangaritza Canton carry out management audits regularly, observing the Internal Control